PKM Peningkatan Produktifitas Kambing Melalui Teknologi Pakan Serasi dan Optimalisasi Limbah Peternakan Di Kelompok Ternak Al. Jauhar, Sorong, Papua Barat - Latifah Latifah; Yusup Sopian; Yusnita La Goa; Eva Maya Sari; Sitti Hadija Samual; Muh. Andika Prasetia (Jurnal Abdimasa Pengabdian Masyarakat, 2023)
Al. Jauhar group is located in Warmon Kokoda, Aimas District, Sorong Regency, West Papua. This group has 31 goats. The maintenance system carried out by this group is the cut and curry system. Goat farmers do not know how to provide good feed for their goats. The breeders still provide makeshift feed without paying attention to the nutritional needs of the goats. This causes the productivity of goats is not optimal. They are also unfamiliar with the provision of suitable feed with a specific average daily gain (ADG) target and feed formulations to improve the quality of goat feed. Another problem faced by Al. Jauhar is goat waste. Manure waste is left unmanaged, causing the cage to smell like ammonia. To overcome partner problems, the programs offered are in the form of training in providing compatible feed, solid waste treatment, and processing of goat livestock liquid waste. Implementing the community partnership program uses a participatory approach and action involving the community and government officials. The results achieved in this activity are increasing residents' knowledge in the provision of a suitable feed, processing solid waste, and processing goat livestock liquid waste.